1988
DOI: 10.1128/jvi.62.3.847-850.1988
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of human polymorphonuclear leukocytes to herpes simplex virus-infected fibroblasts mediated by antibody-independent complement activation

Abstract: Herpes simplex virus (HSV)-infected cells can activate the human complement system without interference of specific anti-HSV antibodies. Analysis by flow cytometry showed that C3-like molecules were deposited on the membrane of the infected cell when incubated with human serum without specific antibodies. Depletion of calcium to block the classical pathway of the complement system had no effect on fluorescence intensity. The complement activation could be blocked by chelating both calcium and magnesium or by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 27 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…a complex of glycoprotein E (gE; encoded by the US8 gene) and gI (encoded by the US7 gene) forms an Fc receptor on the surface of infected cells and virions, and the Fc receptor forms antibody bipolar bridges resulting in the escape from neutralization of virions and infected cells by complement and antibody-dependent killer cells (Para et al , 1982 ; Johansson et al , 1986 ; Johnson & Feenstra, 1987 ; Frank & Friedman, 1989 ). Also, complement activity is suppressed by gC (encoded by UL44), which is a C3b receptor (Friedman et al , 1984 ; McNearney et al , 1987 ; Van Strijp et al , 1988 ). ICP47, one of the immediate-early proteins encoded by the US12 gene, inhibits antigen presentation on the surface of infected cells by inhibition of peptide transporter (TAP), mediating the escape from cytotoxic T cells (York et al , 1994 ; Früh et al , 1995 ; Ahn et al , 1996 ; Tomazin et al , 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…a complex of glycoprotein E (gE; encoded by the US8 gene) and gI (encoded by the US7 gene) forms an Fc receptor on the surface of infected cells and virions, and the Fc receptor forms antibody bipolar bridges resulting in the escape from neutralization of virions and infected cells by complement and antibody-dependent killer cells (Para et al , 1982 ; Johansson et al , 1986 ; Johnson & Feenstra, 1987 ; Frank & Friedman, 1989 ). Also, complement activity is suppressed by gC (encoded by UL44), which is a C3b receptor (Friedman et al , 1984 ; McNearney et al , 1987 ; Van Strijp et al , 1988 ). ICP47, one of the immediate-early proteins encoded by the US12 gene, inhibits antigen presentation on the surface of infected cells by inhibition of peptide transporter (TAP), mediating the escape from cytotoxic T cells (York et al , 1994 ; Früh et al , 1995 ; Ahn et al , 1996 ; Tomazin et al , 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, however, it was suggested that IAV enters neutrophils by phagocytosis of infected apoptotic epithelial cells [42]. Similarly, neutrophils were shown to phagocytose HSV by infected fibroblasts [43] and CMV by infected endothelial cells [44], thus contributing to viral clearance or dissemination, as discussed subsequently.…”
Section: Phagocytosis Of Infectious Agents and Antiviral Programmingmentioning
confidence: 94%
“…Neutrophils may also act indirectly by producing cytokines (4,31), which in turn recruit other effector cells such as T cells and macrophages to the site of virus infection. Finally, neutrophils may collaborate with other defensive factors such as antibody (19,23,45) or complement (52,53) to kill virus-infected cells via cellular cytotoxicity reactions.…”
Section: Fig 4 Effect Of Mab Rb6mentioning
confidence: 99%
“…However, it is the neutrophil that initially infiltrates the cornea, and it is this cell that remains the predominant cell type during the development of herpes stromal keratitis (HSK) (36,37,56). Neutrophils have been shown in vitro to adhere to HSV-infected cells after complement activation (53) and to phagocytose antibody-coated (1,47,54) but not complementcoated (55) herpes virions. Currently, it is not known what effect, if any, neutrophils have in limiting HSV-1 growth in vivo.…”
mentioning
confidence: 99%